IMPLEMENTASI PERMAINAN TRADISIONAL DALAM MENGEMBANGKAN NILAI-NILAI AGAMA DAN MORAL ANAK USIA DINI Hilda Z - Hilda Zahra Lubis (Universitas Pendidikan Ganesha, 2023)
The development of religious and moral values in early childhood in kindergarten is still relatively low. Children are not yet able to demonstrate behavior and attitudes in this development. This is because playing while learning is less associated with traditional games. Therefore, this research aims to describe the application of traditional games and the development of religious and moral values as well as supporting and inhibiting factors for early childhood in kindergarten. The type of research used is qualitative research with a humanistic approach model, the subject of this research. There were 15 children aged 5-6 years, and the data collection techniques used were observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and concluding. The results of this research show that the application of the traditional games Congklak, Map and Seek, engklek, jump rope, and bakelan was programmed by adapting to the themes and sub-themes found in kindergarten. The application results show the development of religious and moral values in early childhood. Even though its implementation cannot be separated from supporting and inhibiting factors, the teacher can overcome this. It is hoped that the results of this research can contribute to playing while learning activities by preserving traditional games for educational institutions and especially early childhood The application results show the development of religious and moral values in early childhood. Even though its implementation cannot be separated from supporting and inhibiting factors, the teacher can overcome this. It is hoped that the results of this research can contribute to playing while learning activities by preserving traditional games for educational institutions and especially early childhood The application results show the development of religious and moral values in early childhood. Even though its implementation cannot be separated from supporting and inhibiting factors, the teacher can overcome this. It is hoped that the results of this research can contribute to playing while learning activities by preserving traditional games for educational institutions and especially early childhood.